Investigation of Farmland Soil and Wheat Heavy Metal Contamination Character in Jinding of Lanping. Issue 1 (February 2021) - Zou, Liling; Li, Changsheng; Lang, Xuewei
Abstract: The contents of Cd and Pb in soil and wheat in Jinding of Lanping in Yunnan were investigated and sampled. And single pollution index method, comprehensive pollution index method and correlation analysis were used to evaluate heavy metal contamination in wheat and soil. Zone A is in the upper reaches of the Pijiang River, and the zone does not contain large mines, where soil in the farmland is not polluted by the heavy metals Cd and Pb. The soil in zone B is slightly polluted by Cd and Pb, and the over-standard rate of the Cd of the samples measured is 75%, and the over-standard rate of the Pb of the soil is 25%. The condition of soil polluted by two heavy metals is Cd > Pb, and the heavy metal pollution of the soil in this Zone is mainly affected by mining activities. Zone C is in the lower reaches of the Pijiang River, and the soil in Zone C is not polluted by Cd and Pb. The content of Cd and Pb in the wheat in Zone A reached the standard and was not polluted. The wheat in Zone B was not polluted by Cd and Pb. Although Cd and Pb in the soil in this Zone was over-standard, it could be concluded that Cd and Pb in the soil did not migrate to wheat. The wheat in Zone C was not contaminated by Cd and Pb.